SP8.2.1 Robotic versus laparoscopic left lateral hepatic sectionectomy: a systematic review and meta-analysis. (9th August 2022) - Hajibandeh, Shahin; Hajibandeh, Shahab; Qayum, Mohammed Kaif; Dosis, Alexios
Abstract: Aims: To evaluate comparative outcomes of robotic and laparoscopic left lateral hepatic sectionectomy (LLS). Methods: A systematic search of PubMed, Web of Science, EMBASE and bibliographic reference lists with application of a combination of free text and controlled vocabulary search adapted to thesaurus headings, search operators and limits was conducted. Overall, minor (Clavien–Dindo gradeIII) postoperative complications, mortality, volume of blood loss, conversion to an open procedure, procedure time, length of hospital stay, cost-effectiveness, and R1 resection were the evaluated outcome measures. Results: Seven comparative observational studies reporting a total of 319 patients of whom 150 underwent robotic LLS and the remaining 169 patients underwent laparoscopic LLS were included. The robotic approach was associated with significantly longer procedure time (MD: 29.40 minutes, p=0.01) and higher cost (MD: $4170, p<0.00001) compared to the laparoscopic approach. There was no significant difference in overall postoperative morbidity (OR: 1.29, p=0.62), Clavien-Dindo grade <III (OR: 1.65, p=0.49), Clavien-Dindo grade > III (OR: 1.18, p=0.85), perioperative mortality (RD: 0.00, p=1.00), volume of blood loss (MD: 1.96 mls, p=0.91), conversion to an open procedure (RD: -0.02, p=0.46), length of hospital stay (MD: 0.22 day, p=0.52) or R1 resection (RD:0.00, p=1.00) between two groups. Conclusions: Meta-analysis of the best available evidence (level 2) demonstrated that robotic LLS is associated with significantly longer procedure time and higher cost and similar perioperative outcomes compared to the laparoscopic approach. Future randomised studies are required to evaluate short-term perioperative, long-term oncological and surgeon-centred outcomes.